Effect of trimetaphosphate and fluoride association on hydroxyapatite dissolution and precipitation in vitro - Delbem, Alberto Carlos Botazzo [UNESP] (2014)
The present study analyzed the action of sodium trimetaphosphate (TMP) and/or fluoride on hydroxyapatite. Hydroxyapatite powder was suspended in different solutions: deionized water, 500 µg F/mL, 1,100 µg F/mL, 1%TMP, 3%TMP, 500 µg F/mL plus 1%TMP and 500 µg F/mL plus 3%TMP. The pH value of the solutions was reduced to 4.0 and after 30 min, raised to 7.0 (three times). After pH-cycling, the samples were analyzed by X-ray diffraction and infrared spectroscopy. The concentrations of calcium fluoride, fluoride, calcium and phosphorus were also determined. Adding 1% or 3% TMP to the solution containing 500 µg F/mL produced a higher quantity of calcium fluoride compared to samples prepared in a 1,100 µg F/mL solution. Regarding the calcium concentration, samples prepared in solutions of 1,100 µg F/mL and 500 µg F/mL plus TMP were statistically similar and showed higher values. Using solutions of 1,100 µg F/mL and 500 µg F/mL plus TMP resulted in a calcium/phosphorus ratio close to that of hydroxyapatite. It is concluded that the association of TMP and fluoride favored the precipitation of a more stable hydroxyapatite.